Altered Gut Microbiota as an Auxiliary Diagnostic Indicator for Patients With Fracture-Related Infection - Zhao, Xingqi; Tang, Wenli; Wan, Haoyang; Lan, Zixin; Qin, Hanjun; Lin, Qingrong; Hu, Yanjun; Yu, Guangchuang; Jiang, Nan; Yu, Bin (Frontiers in Microbiology, 2022)
Preoperative diagnosis of fracture-related infection (FRI) is difficult for patients without obvious signs of infection. However, specific profiles of gut microbiota may be used as a potential diagnostic tool for FRI as suggested by previous study. The faecal microbiome was compared between 20 FRI patients (FRI group), 18 fracture healed patients (FH group) and 12 healthy controls (HC group) included after collection of faecal samples and evaluation. The α and β diversity indices were used to characterize the faecal microbiome. Dysbiosis Indexes were constructed based on the characteristic high-dimensional biomarkers identified in the faecal microbiota from the 3 groups by linear discriminant analysis and generalized linear model analysis to quantify the dysbiosis of faecal microbiota. The effectiveness of α and β diversity indices and Dysbiosis Indexes was assessed in distinguishing the faecal microbiome among the 3 groups. The influences of serum inflammatory factors on gut microbiota were also addressed. The α diversity indices were significantly different between the 3 groups, the highest in HC group and the lowest in FRI group (P < 0.05). The β diversity indices showed significant phylogenetic dissimilarity of gut microbiome composition among the 3 groups (P < 0.001). The Dysbiosis Indexes were significantly higher in FRI group than in FH and HC groups (P < 0.001). The area under Receiver operating characteristic curve showed the characteristics of gut microbiota; and the gut microbiota was found as effective in distinguishing the 3 groups. The dysbiosis in the FRI patients was associated with systemic inflammatory factors. In addition, significant differences in the gut microbiota were not observed between the FRI patients with versus without sinus tract or pus before operation. Since FRI patients, with or without sinus tract or pus, have a characteristic profile of gut microbiota, their gut microbiota may be used as an auxiliary diagnostic tool for FRI suspected.